Ética como Método e os Significados do Ideal (II): Uma Crítica da Filosofia Moral de Mead - Viale, Claudio (Cognitio: Revista de Filosofia, 2012)
This work is the second part of my research on Mead's philosophy. While the heart of the first article (Viale, 2008 a) was a descriptive reconstruction of Mead's theses on moral philosophy, my current objective is to point out and criticize some shortcomings I have found in it. The core of my criticism is that a tension within Mead's moral philosophy exists and I try to show how this tension works. Particularly, I think there is a necessary but unrecognized tension between the Meadean conceptions of ethics as a method and of an ideal world. The lack of acknowledgment of this tension, caused mainly by Mead's shortcomings regarding his conception of ideal, entails a contradiction within Mead's practical philosophy: sometimes, Mead's methodological dictum seems to require a democratic background to work; sometimes,Mead conceives his methodological dictum working in any kind of normative background. To carry out this task I will present two lines of argument: that Mead’s conceptions of ethics as a method and ideal world imply different kinds of theoretical commitments; on the other hand, that Mead’s conception of ideal world cannot coherently arise from his conception of method as he argues. In order to develop my hypothesis, I have divided this article into four parts: first of all I present the theoretical background of the relationships between ethics as a method and the Meadean ideal world; in the second part I attempt to show why a necessary tension between ethics as a methodand the ideal world exists; in the third part I argue why Mead’s ideal world cannot coherently spring from his conception of method; finally, I present my conclusions.